1980
DOI: 10.1007/bf00236664
|View full text |Cite
|
Sign up to set email alerts
|

Perception of images moving at saccadic velocities during saccades and during fixation

Abstract: During saccadic eye movements, images of external objects move rapidly across the retina. Small, unpredictable displacements imposed upon a target moving at saccadic velocity were detected with equal accuracy when (1) the retinal image velocity was caused by an eye movement, or (2) when the same velocity was produced during fixation (simulated saccadic conditions). The results provide no evidence of a specific non-visual suppression of vision during saccades, nor of any other compensatory modification of affer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Although temporal masking is often attributed to stimuli covering the entire display (Castet et al, 2002) or even the entire visual field (Campbell & Wurtz, 1978), it is possible to achieve similar effects with just simple flashes of light without a necessary spatial or retinal overlap, an effect attributed to meta-contrast masking (Matin et al, 1972). Interestingly, this mechanism has been shown to be equally effective both during real and simulated saccades (Brooks et al, 1980;Brooks et al, 1981). The absence of post-saccadic masking, however, is not representative for the circumstances of natural vision, where every intra-saccadic input is followed (and thus masked) by a more reliable and stable retinal image (Castet, 2010).…”
Section: Visual Processing Of Intra-saccadic Motion Smearmentioning
confidence: 99%
“…Although temporal masking is often attributed to stimuli covering the entire display (Castet et al, 2002) or even the entire visual field (Campbell & Wurtz, 1978), it is possible to achieve similar effects with just simple flashes of light without a necessary spatial or retinal overlap, an effect attributed to meta-contrast masking (Matin et al, 1972). Interestingly, this mechanism has been shown to be equally effective both during real and simulated saccades (Brooks et al, 1980;Brooks et al, 1981). The absence of post-saccadic masking, however, is not representative for the circumstances of natural vision, where every intra-saccadic input is followed (and thus masked) by a more reliable and stable retinal image (Castet, 2010).…”
Section: Visual Processing Of Intra-saccadic Motion Smearmentioning
confidence: 99%
“…The importance of masking during ordinary viewing was also recently emphasized by Brooks, Yates, and Coleman (1980), who showed that vision for moving images during saccades may be as sensitive and accurate as during fixation if preand postsaccadic masking influences are carefully eliminated.…”
mentioning
confidence: 97%
“…Dennett suggests, and I agree, that this expectation is based on a folk-theoretical belief that vision presents us with a relatively uniformly clear and colored world in which objects are easily distinguished. But, as this simple demonstration shows, as do other more rigorous experiments, e.g., Brooks et al (1980), this is at best only true of the foveated world, and even then with some exceptions (Caplovitz et al, 2008). 2 …”
Section: The Occasionality Problem and Unconscious Representations Ofmentioning
confidence: 66%